Fighting sports, gender, and the commodities of violence: heavy bag heroines - Collins, Victoria E. (Lexington Books, 2021)
Finding boxing in a strip-mall -- From Amazonians to cardio classes : women, consumerism, and combat sports -- Commodifying and the woman boxer : popular culture, media, and the sexualized fighter -- Fighting tough...but not too tough -- There are only three rules of fight club, "No spectators, no social media, and no boob shots!" -- Sparring like men? : gender maneuvering and the emotional work of getting in the ring -- Violence, safety, and self-defense : unpacking the narrative that boxing is self-defense -- The female fight : sport and the spectacle.